The Dynamics of Millennial Consumer Behavior in Online Shopping Decision-Making on the Shopee Marketplace with Scarcity Perception as a Moderating Variable - Irience R. A. Manongga; Yanti S. Giri (Journal of Management and Business Innovation, 2025)
In recent years, online shopping activity among millennials has shown a very significant increase. The development of digital technology, the intensification of promotional strategies, and lifestyle trends demanding convenience and speed have also contributed to the dominance of this group as active users of various e-commerce platforms, including Shopee. This condition underscores the importance of an in-depth study of the determinants influencing purchasing decisions within this consumer segment. This study aims to analyze the influence of the millennial generation lifestyle on purchasing decisions, with scarcity perception acting as a moderating variable. A total of 96 respondents were involved in this study using the Lemeshow technique and purposive sampling. Data analysis was performed using simple regression and multiple regression analysis (MRA). The research findings indicate that lifestyle has a positive and significant influence on Shopee users' purchase decisions in Kupang City (b = 0.759; p = 0.000; R = 0.724). On the other hand, the moderation test of scarcity perception yielded a negative and non-significant effect (b = -0.001; p = 0.087). However, an R² value of 0.733 indicates that the presence of the moderating variable still contributes to strengthening the relationship between lifestyle and purchase decisions.